The Meaning of the Primacy of Education in the Islamic Education System - Fauzah, Fitriyah (MultiTech Publisher, 2023)
There are so many who understand the meaning of Education, see in terms of language, universally and philosophically, even religion also interprets its own Education and interprets various kinds of words that can be described. This study aims to explore the meaning of religious education based on Islamic Education. This research uses qualitative methods through the views of religionists who understand the meaning of education. The results showed the understanding of Tarbiyah in Islamic Education, the content and scope of Islamic Education, the tasks and functions of Islamic Education, the methods and processes of Islamic Education. This finding shows the importance of recognizing the meaning of education in the Islamic Education system. This research has implications for humans who carry out education divinely, rububiyah, and uluhiyah based on the Qur'an and hadith.